2012
DOI: 10.1177/1741143212456912
|View full text |Cite
|
Sign up to set email alerts
|

Research Use in School District Central Office Decision Making

Abstract: The current educational policy climate in the USA places immense pressure on school district central offices to use evidence to inform their decisions in order to improve student learning. In light of both the expectations of evidence-based decision making and the significance of central offices in supporting teaching and learning, there is considerably little understanding of whether, how and why central office decision makers use research evidence to support educational decisions. Through an embedded case st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(69 citation statements)
references
References 26 publications
3
66
0
Order By: Relevance
“…Scholars have increasingly focused their research on understanding the practice of central offices and the administrators who work within them (Coburn, Toure, & Tamashita, 2009;Farley-Ripple, 2012;Honig, 2003Honig, , 2006Honig, , 2008Honig, , 2012Honig & Rainey, 2015;McLaughlin & Talbert, 2003;Swinnerton, 2007). Scholars suggest that leadership practices within central offices differ in significant ways from that of leadership practice in schools (Honig, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Scholars have increasingly focused their research on understanding the practice of central offices and the administrators who work within them (Coburn, Toure, & Tamashita, 2009;Farley-Ripple, 2012;Honig, 2003Honig, , 2006Honig, , 2008Honig, , 2012Honig & Rainey, 2015;McLaughlin & Talbert, 2003;Swinnerton, 2007). Scholars suggest that leadership practices within central offices differ in significant ways from that of leadership practice in schools (Honig, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…We know from extant research that decision making is a social process of interpretation, negotiation, and persuasion (Coburn, Toure & Yamashita, 2008;Coburn, Bae & Turner, 2008). In this process, data do not speak for themselves; rather, people must actively make meaning of them and construct implications for action (Coburn & Talbert, 2006;Farley-Ripple, 2012;Kennedy, 1982). How educators use data in decision making is influenced by individual and collective beliefs, which shape how people interpret data and their consequences for policy solutions (Cho & Wayman, 2014;Park, Daly, & Guerra, 2013), as well as by the dynamics of social interaction (Spillane, 2012).…”
Section: The Need For a New Approachmentioning
confidence: 99%
“…This school leaders' self-reported evidence-informed school leadership was not supported by the use of either school data or (academic) evidence. All in all, this study's findings indicate an even broader interpretation of evidence than that encountered in comparable studies on research use by U.S. school district leaders (Farley-Ripple, 2012;Penuel, Farrell, et al, 2016). Based on the findings of these U.S. studies, Penuel et al have already suggested "the need for a more nuanced understanding of the differences between leaders' conceptions of research evidence and researchers' conceptions identified in earlier research" (Penuel, Farrell, et al, 2016).…”
Section: What Kind Of Evidence Do School Leaders Use In Their School mentioning
confidence: 52%
“…To this day, however, research evidence and school data often represent two separate fields of activity and study (Brown, Schildkamp, & Hubers, 2017). That said, studies have approached evidence use more comprehensively by asking practitioners what kind of evidence they find useful (e.g., Farley-Ripple, 2012;Penuel, Farrell, Allen, Toyama, & Coburn, 2016). These studies suggested that practitioners use a wider array of sources than either research evidence or school data alone.…”
Section: Evidencementioning
confidence: 99%
See 1 more Smart Citation